Frugal sustainability: A new perspective to foster corporate sustainability - Timo Achtelik; Cornelius Herstatt; Rajnish Tiwari (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2022)
Frugal innovations are increasingly considered in the context of sustainability and are seen to have promising potential for the realization of global sustainability goals. So far, the discourse has focused on the question of whether and how frugal innovations contribute to sustainable development without presenting concrete guidelines and principles. Through a systematic literature review guiding principles are therefore derived, conceptualized in the motivational context of emerging and industrialized economies and empirically illustrated using the example of Western automotive companies. The principles can be used to further substantiate the link between frugal innovations and corporate sustainability as well as to use them for the development of green(er) innovation.
Keywords: 330; Frugal Innovation; Frugal Sustainability; Corporate Sustainability; Automotive